Clofarabine salvage therapy before allogeneic hematopoietic stem cell transplantation in patients with relapsed or refractory AML: results of the BRIDGE trial - Middeke, Jan Moritz; Klein, Stefan (Leukemia, 2016)
In patients with relapsed or refractory (r/r) acute myeloid leukemia (AML), long-term disease control can only be achieved by allogeneic hematopoietic stem cell transplantation (HSCT). We studied the safety and efficacy of clofarabine-based salvage therapy. The study was designed as phase II, multicenter, intent-to-transplant (ITT) study. A total of 84 patients with r/r AML were enrolled. All patients received at least one cycle of CLARA (clofarabine 30 mg/m2 and cytarabine 1 g/m2, days 1-5). Chemo-responsive patients with a donor received HSCT in aplasia after first CLARA. Generally, HSCT was performed as soon as possible. The conditioning regimen consisted of clofarabine (4 × 30 mg/m2) and melphalan (140 mg/m2). The median patient age was 61 years (range 40-75). On day 15 after start of CLARA, 26% of patients were in a morphologically leukemia-free state and 79% exposed a reduction in bone marrow blasts. Overall, 67% of the patients received HSCT within the trial. The primary end point, defined as complete remission after HSCT, was achieved by 60% of the patients. According to the ITT, overall survival at 2 years was 43% (95% confidence interval (CI), 32-54%). The 2-year disease-free survival for transplanted patients was 52% (95% CI, 40-69%). Clofarabine-based salvage therapy combined with allogeneic HSCT in aplasia shows promising results in patients with r/r AML.